(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The study aimed to analyze the concept of the budget of the programs and performance, the methodology of its application and the advantages obtained from it and to find out the deficiencies in the traditional budgets currently applied. The common factor of all the concepts of the program budget and performance was based on linking the programs of government units with the general objectives of the state. Accounting for the money to focus on the services provided by government units in the output data class The study also ranked the priorities of the transformation in accordance with the vision and experience of international institutions and countries that have developed the budget method of She has. The study gained its importance by addressing the analysis and the conclusion of the balance of programs and performance and the achievements of many of the pros that can be used in the development of the performance of Iraqi universities as the cornerstone of the development process in society. The study concluded several results, the most important of which was the inability of the traditional method of balancing the Iraqi universities (Babylon University) to be an effective tool for planning and control, and that the standards and indicators of performance required to be developed to be able to meet the performance of universities and most recommended by the study is the adoption of the Ministry of Higher Education and Research Scientific evaluation of programs and performance because they have a role in the development and analysis of strategic plans and linking them in the goals.